The evolution characteristics of diamondoids in coal measures and their potential application in maturity evaluation - Zhai, Jia; Cao, Zhenglin; Fang, Chenchen; Yuan, Yilin; Wu, Wei; Liu, Jinzhong (Frontiers in Earth Science, 2023)
In this study, gold tube thermal simulation experiments were carried out on the soluble components (extracts) and insoluble components (extracted coal measures mudstone) in the coal measures mudstone, and the diamondoid compounds in the pyrolysis products were quantitatively analyzed. The results show that the diamondoid compounds in the extracts and the extracted coal measure mudstone have undergone the process of formation and decomposition during the thermal evolution. Based on the quantitative composition of the extracts and the extracted coal measure mudstone in the coal measure mudstone, the evolution characteristics of diamondoid compounds in the calculated coal measure mudstone are basically consistent with the evolution characteristics of diamondoid compounds in the gold tube thermal simulation experiment of the untreated coal measure mudstone, indicating that the formation of diamondoid compounds is mainly controlled by the original material source. Some diamondoid maturity parameters (MAI, EAI, TMAI-1) in coal measure mudstone are consistent with the parameter evolution characteristics in marine shale. These parameters can be used to calculate the maturity (vitrinite reflectance) of marine shale instead of equivalent vitrinite reflectance. In addition, the evolution characteristics and some diamondoid maturity parameters in the extract and the extracted coal measures mudstone show a good linear relationship, but the specific characteristics are different, which may identify kerogen cracking and secondary cracking of crude oil.